2013
DOI: 10.1371/journal.pone.0076966
|View full text |Cite
|
Sign up to set email alerts
|

An Interactive Association of Advanced Glycation End-Product Receptor Gene Four Common Polymorphisms with Coronary Artery Disease in Northeastern Han Chinese

Abstract: BackgroundGrowing evidence indicates that advanced glycation end-product receptor (RAGE) might play a contributory role in the pathogenesis of coronary artery disease (CAD). To shed some light from a genetic perspective, we sought to investigate the interactive association of RAGE gene four common polymorphisms (rs1800625 or T-429C, rs1800624 or T-374A, rs2070600 or Gly82Ser, and rs184003 or G1704A) with the risk of developing CAD in a large northeastern Han Chinese population.Methodology/Principal FindingsThi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…Finally, 16 articles meeting the inclusion criteria were preserved. [1732] A flow diagram of the literature selection process is shown in Fig. 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, 16 articles meeting the inclusion criteria were preserved. [1732] A flow diagram of the literature selection process is shown in Fig. 1.…”
Section: Resultsmentioning
confidence: 99%
“…[16] Some studies in humans and animals have yielded conflicting results concerning the potential role of the RAGE Gly82Ser polymorphism in the pathogenesis of atherosclerosis. Several studies have indicated that Gly82Ser polymorphism is a possible risk factor for the development of CAD, [17,18] while others failed to specifically link this variant to CAD. [19,20] Meanwhile, the role of Gly82Ser polymorphism in IS susceptibility remains controversial.…”
Section: Introductionmentioning
confidence: 99%
“…The haplotype frequencies of five examined polymorphisms in DNMT1 gene were estimated as previously reported [ 22 ]. Only haplotype with frequency ≥3% was considered in haplotype analyses.…”
Section: Methodsmentioning
confidence: 99%
“…21,22 In fact, all study patients in this study are local residents of Han Chinese descent from northeast China, and they are characterized by genetic homogeneity and geographic stability, and are probably more uniform in their environmental exposures, including the habitual dietary intake of high salt and high fat. 15 Even so, the results of this association study must be viewed with great caution given that our effect estimates were based on 679 patients with CAD and 686 controls, this sample size possibly being insufficient to draw a firm conclusion. However, a priori power calculation of our sample size convinced us to have >94% power to detect the significant genetic markers of realistic effect sizes.…”
Section: Discussionmentioning
confidence: 89%
“…14,15 Written informed consent was obtained from each patient at enrollment. This study received approval from the ethics committee of Dalian Medical University and was conducted in agreement with the guidelines of Declaration of Helsinki.…”
Section: Study Populationmentioning
confidence: 99%